2017
DOI: 10.1155/2017/4627928
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three Biochars as Adsorbents on Soils Adsorbing Ammonium Nitrogen in Biogas Slurry

Abstract: The increasing concern of biogas slurry disposal and nitrogen loss in soils has brought back the interest in using biochar as an adsorbent of biogas slurry in soils. Three types of biochars, commercial activated carbon, pyrolysis productions derived from rice husk, and nut shell, were added as adsorbents in two types of soils (sandy and loamy) at solid weight ratio of 5%, 10%, 15%, and 20% to investigate the effects of biochars on soils adsorbing ammonium nitrogen (NH 4 + -N) in biogas slurry using oscillation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Many studies have revealed the application potential of BR‐derived biochar, for example, efficiently sorbing pollutant (Sun et al, 2013) and NH 4 + (Wang et al, 2017). However, the impact of BR biochar on the soil bacteria community remains unclear, which limits the field‐scale application of BR‐derived biochar.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have revealed the application potential of BR‐derived biochar, for example, efficiently sorbing pollutant (Sun et al, 2013) and NH 4 + (Wang et al, 2017). However, the impact of BR biochar on the soil bacteria community remains unclear, which limits the field‐scale application of BR‐derived biochar.…”
Section: Introductionmentioning
confidence: 99%